2022
DOI: 10.1111/acv.12772
|View full text |Cite
|
Sign up to set email alerts
|

Occupancy models reveal potential of conservation prioritization for Central American jaguars

Abstract: Understanding species-environment relationships at large spatial scales is required for the prioritization of conservation areas and the preservation of landscape connectivity for large carnivores. This endeavour is challenging for jaguars (Panthera onca), given their elusiveness, and the local nature of most jaguar studies, precluding extrapolation to larger areas. We developed an occupancy model using occurrence data of jaguars across five countries of Central America, collected from camera-trap studies of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
2
1
Order By: Relevance
“…Thus, we suggest using faster PIR camera brands in future surveys to improve Andean tiger cat detectability. Contrary to the trends observed for other neotropical small felids, we found that the camera trap effort showed no relevant effect on the detectability of the Andean tiger cat [ 5 , 30 , 61 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, we suggest using faster PIR camera brands in future surveys to improve Andean tiger cat detectability. Contrary to the trends observed for other neotropical small felids, we found that the camera trap effort showed no relevant effect on the detectability of the Andean tiger cat [ 5 , 30 , 61 ].…”
Section: Discussioncontrasting
confidence: 99%
“…We fit each model with uninformative priors and ran three Markov Chain Monte Carlo (MCMC) samplers of 30,000 iterations, from which the first half was discarded as burn-in. Additionally, we calibrated the models with an acceptance sample (adapt_delta) of 0.99 for the adaptation period of the MCMC sampling [ 61 ]. A value of 0.99 for adapt_delta means that the algorithm will explore the parameter space more thoroughly during adaptation, which can lead to better quality posterior samples [ 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…Site occupancy models offer valuable insights into understanding how speci c variables in uence the occupancy of a species, aiding in the strategic prioritization of areas for conservation efforts (Calderón et al 2022). We employed single-season single-species occupancy models to estimate two critical parameters: the probability of detection (p) and the probability of occupancy (ψ) (MacKenzie et al 2002).…”
Section: Occupancy Modellingmentioning
confidence: 99%